Strategi Perencanaan Kepala Sekolah Dalam Pembiayaan Pendidikan Untuk Peningkatan Raport Pendidikan di SDN Sambeng Kecamatan Todanan - Permono, Gilar Kholiq; Wanodya , Anora; Wahyuningsih, Siti; Rojaenah, Siti; Ayu Nyoman, Ngurah (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study analyzes the financial planning strategies of school principals in improving the quality of education as reflected in the Education Report. The case study at SDN Sambeng explores participatory, transparent, and quality-oriented financing practices. The results show that stakeholder involvement in budget preparation, flexibility in fund allocation, and a focus on improving teacher capacity and learning resources contribute to improving school quality indicators. Challenges such as limited BOS funds and bureaucratic constraints are overcome with adaptive and innovative leadership. In addition, the principal seeks to optimize alternative funding sources through grants, community partnerships, and alumni support. The implementation of these strategies increases the effectiveness of budget management and strengthens academic programs that are oriented towards student learning outcomes. These findings provide insights for principals and policy makers in designing effective education financing strategies to strengthen the quality of learning and achieve the target of improving academic achievement.